The Gymnaestrada in Zagreb ( July 10th-14th) and the Congress for Physical education (July 14th-17th, 1957) (Fiep Bulletin - online, 2015)
In the Style of the Lingiads held in 1939 and 1949 the Federation Internationale de Gymnastique (FIG)  decided to hold every fourth year a similar gymnastic Festival, which received the name “gymnaestrada”.